2021
DOI: 10.3390/ijms22020910
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Knowledge of the Underlying Airway Remodeling Mechanisms in Chronic Rhinosinusitis Based on the Endotypes: A Review

Abstract: Chronic rhinosinusitis (CRS) is a chronic inflammatory condition of the nasal and paranasal sinus mucosa that affects up to 10% of the population worldwide. CRS is the most representative disease of the upper respiratory tract where airway remodeling occurs, including epithelial damage, thickening of the basement membrane, fibrosis, goblet cell hyperplasia, subepithelial edema, and osteitis. CRS is divided into two phenotypes according to the presence or absence of nasal polyps: CRS with nasal polyp (CRSwNP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 130 publications
(61 reference statements)
0
23
0
2
Order By: Relevance
“…Its importance is widely investigated in recalcitrant cases. In CRS, tissue remodeling appears in various forms, including EMT, subepithelial fibrosis, goblet cell hyperplasia, hypertrophy of bronchial myocytes, submucosal angiogenesis, and increased extracellular matrix deposition, depending on the type of inflammation [ 10 ]. Among them, EMT is a consistent phenomenon in the mucosal epithelium of CRS regardless of the type of inflammation or presence of nasal polyps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its importance is widely investigated in recalcitrant cases. In CRS, tissue remodeling appears in various forms, including EMT, subepithelial fibrosis, goblet cell hyperplasia, hypertrophy of bronchial myocytes, submucosal angiogenesis, and increased extracellular matrix deposition, depending on the type of inflammation [ 10 ]. Among them, EMT is a consistent phenomenon in the mucosal epithelium of CRS regardless of the type of inflammation or presence of nasal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue remodeling refers to the structural change that is caused by a persistent inflammatory response. Airway remodeling is characterized by inflammatory cell infiltration, basement membrane thickening, angiogenesis, goblet cell hyperplasia, edema, and fibrosis [ 10 ]. Tissue remodeling can be associated with pathological changes in CRS in the respiratory epithelium, lamina propria, and submucosa.…”
Section: Introductionmentioning
confidence: 99%
“…However, further research demonstrated that immunologic profile is much more complex, demonstrating that there is some overlap and endotypes may coexist in the same patient. In fact, non-eosinophilic inflammation dominated by Th1/Th17 pathways may be associated with CRSwNP and CRSsNP patients may express a Type 2 cytokine profile [12][13][14][15] . Because studies on endotyping provided full insight into the underlying cellular and molecular inflammatory mechanisms associated with CRS 16 , the EPOS 2020 group 1 came into the decision to change the management approach to CRS.…”
Section: Management Based On Phenotyping and Endotyping Of The Diseasementioning
confidence: 99%
“…Moreover, the concept of tissue remodeling has been well established in lower respiratory diseases, such as asthma, that share similar pathological mechanisms with refractory CRS. According to current evidence, tissue remodeling in CRS shows characterized clinical features based on the endotype and continuously occurs during ongoing inflammation [15]. Kao et al reported further evidence that CRS mucous, regardless of phenotype, demonstrated dysregulations of biological processes related to tissue remodeling using proteomic analysis [16].…”
Section: Discussionmentioning
confidence: 99%